Human granulocytotropic anaplasmosis-A systematic review and analysis of the literature. - Sophie Schudel; Larissa Gygax; Christian Kositz; Esther Kuenzli; Andreas Neumayr (PLoS Neglected Tropical Diseases, 2024)
Human granulocytotropic anaplasmosis (HGA) is a zoonotic tick-borne bacterial infection caused by Anaplasma phagocytophilum. While most cases are reported from North America, HGA has been recognized as an emerging disease in several regions of the world in recent decades. Most available data comes from case reports, case series and retrospective studies, while prospective studies and clinical trials are largely lacking. To obtain a clearer picture of the currently known epidemiologic distribution, clinical and paraclinical presentation, diagnostic aspects, complications, therapeutic aspects, and outcomes of HGA, we systematically reviewed the literature and analyzed and summarized the data. Cases of HGA are reported from all continents except from Antarctica. HGA primarily presents as an unspecific febrile illness (88.5% of the cases) often accompanied by thrombocytopenia (71.8% of the cases), abnormal liver injury tests (66.7% of the cases), and leukopenia (49.8% of the cases). Although we found complications reported in a total of 40.5% of the reviewed cases and severe and even life-threatening complications are not infrequent (e.g. acute renal failure 9.8%, multi organ failure 7.5%, ARDS 6.3%, a.o.), sequelae are rare (2.1% of the cases) and lethality is low (3.0% of the cases). Treatment with doxycycline shows a rapid response, with the fever subsiding in the majority of patients within one day of starting treatment. Unlike in human monocytotropic ehrlichiosis (HME), reports of opportunistic infections complicating HGA are rare. HGA during pregnancy does not appear to be associated with unfavorable outcomes. In addition, our analysis provides some evidence that HGA may differ in clinical aspects and laboratory characteristics in different regions of the world. Overall, the data analyzed indicates a non-negligible bias in reporting/publication, so a certain degree of caution is required when generalizing the data.